My musick shall finde thee. Issue 2 (25th November 2022) - Mosher, Lucinda
Abstract : In this essay, I accept scholarly assessments of the theology of Renaissance poet George Herbert (1593–1633) as high sacramental ecclesiology melded with Synod of Dort (1618–19) Calvinism (which I describe briefly). This given, I consider what theological messages we can expect to find in lyrics drawn from Herbert's poetry. I make the point that music can amplify the meaning of a text. I then describe in depth the doctrine taught in three well-known poems when set as a choral anthem.